Medication reconciliation errors in a tertiary care hospital in Saudi Arabia: admission discrepancies and risk factors - Mazhar F; Akram S; Al-Osaimi YA; Haider N. (Centro de Investigaciones y Publicaciones Farmaceuticas, 2017)
Background: Medication reconciliation is a major component of safe patient care. One of the main problems in the implementation of a medication reconciliation process is the lack of human resources. With limited resources, it is better to target medication reconciliation resources to patients who will derive the most benefit from it. Objective: The primary objective of this study was to determine the frequency and types of medication reconciliation errors identified by pharmacists performing medication reconciliation at admission. Each medication error was rated for its potential to cause patient harm during hospitalization. A secondary objective was to determine risk factors associated with medication reconciliation errors. Methods: This was a prospective, single-center pilot study conducted in the internal medicine and surgical wards of a tertiary care teaching hospital in the Eastern province of Saudi Arabia. A clinical pharmacist took the best possible medication history of patients admitted to medical and surgical services and compared with the medication orders at hospital admission; any identified discrepancies were noted and analyzed for reconciliation errors. Multivariate logistic regression was performed to determine the risk factors related to reconciliation errors. Results: A total of 328 patients (138 in surgical and 198 in medical) were included in the study. For the 1419 medications recorded, 1091 discrepancies were discovered out of which 491 (41.6%) were reconciliation errors. The errors affected 177 patients (54%). The incidence of reconciliation errors in the medical patient group was 25.1% and 32.0% in the surgical group (p<0.001). In both groups, the most frequent reconciliation error was the omission (43.5% and 51.2%). Lipid-lowering (12.4%) and antihypertensive agents were most commonly involved. If undetected, 43.6% of order errors were rated as potentially requiring increased monitoring or intervention to preclude harm; 17.7% were rated as potentially harmful. A multivariate logistic regression model showed that patients aged ≥65 years, polypharmacy, and prescriptions for hypoglycemic drugs and warfarin were more likely associated with reconciliation errors. Conclusion: There is a high failure rate in medication reconciliation process in patients admitted to the medical and surgical department. The reconciliation process proves to be a useful tool since nearly half of avoided reconciliation errors were unintentional and had the potential for harm. This strategy, based on our results and the difficulty of applying the process to all patients should be directed primarily to the patients at increased risk of error.